2003
DOI: 10.1016/s1097-2765(03)00356-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Arl1-Dependent Targeting of Homodimeric GRIP Domains to the Golgi Apparatus

Abstract: Golgins are large coiled-coil proteins that play a role in Golgi structure and vesicle traffic. The Arf-like GTPase Arl1 regulates the translocation of GRIP domain-containing golgins to Golgi membranes. We report here the 1.7 A resolution structure of human Arl1-GTP in a complex with the GRIP domain of golgin-245. The structure reveals that the GRIP domain consists of an S-shaped arrangement of three helices. The domain forms a homodimer that binds two Arl1-GTPs using two helices from each monomer. The structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
169
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(177 citation statements)
references
References 60 publications
6
169
1
1
Order By: Relevance
“…Based on data in vitro data from cultured cells transfected with ARFRP1 constructs, we and others have previously suggested that the GTPase is required for targeting of ARL1 and of its effector Golgin-245 to the trans-Golgi network (7)(8)(9)(10)43). The present data provide solid proof for this conclusion in showing that ARL1 dissociated from Golgi membranes to the cytosol in an in vivo knockdown of Arfrp1 (Arfrp1 vilϪ/Ϫ epithelial cells, Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Based on data in vitro data from cultured cells transfected with ARFRP1 constructs, we and others have previously suggested that the GTPase is required for targeting of ARL1 and of its effector Golgin-245 to the trans-Golgi network (7)(8)(9)(10)43). The present data provide solid proof for this conclusion in showing that ARL1 dissociated from Golgi membranes to the cytosol in an in vivo knockdown of Arfrp1 (Arfrp1 vilϪ/Ϫ epithelial cells, Fig.…”
Section: Discussionsupporting
confidence: 82%
“…As predicted from sequence signatures, 22 structural studies of Arf-like and Arf-related GTPases, including Golgi Arl1, 74,75 cilium Arl3 76,77,78 and Arl6 79 and endoplasmic reticulum Sar1 80,81 have now shown that autoinhibition by the N-terminal extension and the interswitch takes place in these GTPases and is released by the displacement of the N-terminus and the toggle of the interswitch. Thus, the allosteric mechanism that uses the displacement of the N-terminal extension as a priming event to autoinhibition release and the remodeling of the interswitch as the means whereby information is propagated to the nucleotide-binding site is probably general to the entire Arf-like family.…”
Section: Regulation Of Bacterial Arfgefs By Membranesmentioning
confidence: 80%
“…We and others recently demonstrated that GRIP Golgins form homodimers through both their GRIP and coiled-coil regions (Panic et al, 2003a;Wu et al, 2004). Similar to p115, GM130 and Giantin, the homodimer of Golgin-97 probably adopt a long rod structure, with its C-terminal GRIP domain anchoring to the TGN membrane through interaction with two Arl1-GTP, whereas its N-terminal globular regions extend into the cytosol to mediate the tethering of retrograde transport vesicles derived from endosomes.…”
Section: Discussionmentioning
confidence: 94%